Extract of Seaweed Codium fragile Inhibits Integrin αIIbβ3-Induced Outside-in Signaling and Arterial Thrombosis - Kim, Tae In; Kim, Yeon-Ji; Kim, Kyungho (Frontiers in Pharmacology, 2021)
Seaweeds are thought to be promising candidates for functional foods and to help prevent thrombotic and related cardiovascular diseases. Codium fragile (Suringer) Hariot has been traditionally used as a culinary ingredient, and it possesses a range of biological activities, including the inhibition of platelet function. However, the mechanism of this inhibition is unclear. The aim of this study was to examine the inhibitory effect of C. fragile in platelet function. The antiplatelet activity of C. fragile on agonist-activated platelet aggregation, granule secretion, calcium mobilization, platelet spreading, and clot retraction were assessed. The phosphorylation of c-Src, Syk, PLCγ2, and several proteins involving in the αIIbβ3 integrin outside-in signaling pathway were also studied in thrombin and CRP-stimulated platelets. The antithrombotic effect was investigated in mice using ferric chloride-induced arterial thrombus formation in vivo. Transection tail bleeding time was used to evaluate whether C. fragile inhibited primary hemostasis. The main components and contents of C. fragile ethanol extract were confirmed by GC-MS analysis. C. fragile significantly impaired agonist-induced platelet aggregation granule secretion, calcium mobilization, platelet spreading, and clot retraction. Biochemical analysis revealed that C. fragile inhibited the agonist-induced activation of c-Src, Syk, and PLCγ2, as well as the phosphorylation of PI3K, AKT, and mitogen-activated protein kinases (MAPKs). The inhibitory effect of C. fragile resulted from an inhibition of platelet αIIbβ3 integrin outside-in signal transduction during cell activation. Oral administration of C. fragile efficiently blocked FeCl3-induced arterial thrombus formation in vivo without prolonging bleeding time. GC-MS analysis revealed that phytol was the main constituent and the total content of isomers was 160.8 mg/kg. Our results demonstrated that C. fragile suppresses not only the inside-out signaling of αIIbβ3 integrin but also outside-in signal transmission. Therefore, C. fragile could be an effective antiplatelet therapeutic candidate.